2021
DOI: 10.1155/2021/5546991
|View full text |Cite
|
Sign up to set email alerts
|

Serum Interleukin‐37 Increases in Patients after Ischemic Stroke and Is Associated with Stroke Recurrence

Abstract: Background. This study seeks to assess interleukin-37 (IL-37) serum level in acute ischemic stroke and the value of predicting 3-month stroke recurrence and functional outcome in acute ischemic stroke. Methods. From January 1, 2018, to June 30, 2019, all consecutive first-ever acute ischemic stroke patients from our hospital, China, were included. Serum samples, clinical information, and stroke severity (defined by the National Institute of Health stroke scale (NIHSS) score) were collected at baseline. Serum I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Increased serum IL-34 levels may be a novel diagnostic and prognostic biomarker in patients with acute ischemic stroke ( 173 ). Increased serum IL-37 in ischemic stroke patients is correlated with stroke recurrence ( 174 ) and 3-month functional prognosis ( 175 ). However, another study has illustrated that IL-37 exert protective effects by modulating post-stroke inflammation in the brain and periphery ( 176 ).…”
Section: Other Ils In Ischemic Strokementioning
confidence: 99%
“…Increased serum IL-34 levels may be a novel diagnostic and prognostic biomarker in patients with acute ischemic stroke ( 173 ). Increased serum IL-37 in ischemic stroke patients is correlated with stroke recurrence ( 174 ) and 3-month functional prognosis ( 175 ). However, another study has illustrated that IL-37 exert protective effects by modulating post-stroke inflammation in the brain and periphery ( 176 ).…”
Section: Other Ils In Ischemic Strokementioning
confidence: 99%
“…In addition, other serum biomarkers, such as serum Copeptin levels, are associated with recurrent stroke events and are predictors of severity at admission and 1-year stroke recurrence in stroke patients ( Tang et al, 2017 ). In addition, other biomarkers such as serum fatty acid binding protein 4 (FABP4) ( Li et al, 2019 ), serum CXCL12 levels ( Gu et al, 2016 ), interleukin-37 ( Zhang et al, 2021 ), and cystatin C ( Liu et al, 2021 ) have been reported to be associated with stroke recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of IL-37 in humans have focused on its role in inflammatory disorders, each of which is characterized by excessive immune activation, e.g., rheumatoid arthritis, systemic lupus erythematosus, and atherosclerosis. In these states, circulating IL-37 levels are elevated relative to healthy controls [ 16 , 32 , 33 , 35 , 38 , 46 , 50 , 54 , 64 , 66 , 67 , 69 , 71 ], presumably as a compensatory physiological response to mitigate the impact of increases in circulating pro-inflammatory cytokines [ 16 , 66 , 67 ]. Indeed, under such conditions, circulating IL-37 often correlates with concentrations of IL-6, TNF⍺, CRP, and/or other pro-inflammatory cytokines [ 16 , 31 , 32 , 46 , 66 , 69 ], as well as with markers of disease severity or progression [ 31 , 38 , 38 , 67 , 71 ].…”
Section: Discussionmentioning
confidence: 99%